2017
DOI: 10.1097/mlr.0000000000000690
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Service Use and the Uptake of Screening Colonoscopies

Abstract: No significant association between anesthesia service use and colonoscopy screening or colorectal cancer screening rates was found, suggesting that more evidence is needed to support the Center for Medicare & Medicaid Services rule change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In fact, Medicare covers anesthesia costs for screening colonoscopies without any deductibles. This policy was intended to increase the uptake of colon cancer screening, despite studies showing that anesthesia use is not associated with any increase in screening rates, 80 but will increase costs. 81 In situations where insurance coverage for anesthesia is denied, patients are charged directly.…”
Section: Computer-assisted Propofol Sedationmentioning
confidence: 99%
“…In fact, Medicare covers anesthesia costs for screening colonoscopies without any deductibles. This policy was intended to increase the uptake of colon cancer screening, despite studies showing that anesthesia use is not associated with any increase in screening rates, 80 but will increase costs. 81 In situations where insurance coverage for anesthesia is denied, patients are charged directly.…”
Section: Computer-assisted Propofol Sedationmentioning
confidence: 99%
“…One of the factors influencing the quality of endoscopy examination is sedation. Several studies on colonoscopy have suggested that sedation improves adenoma detection ( 16), but the evidence is inconsistent (17)(18)(19)(20)(21). Few studies have focused on the association between AA and the rate of lesion detection in patients undergoing EGD screening.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 In contrast, providing mere financial incentives resulted in a modest if any increase in CRC screening uptake. 12,[62][63][64]…”
Section: Facilitatementioning
confidence: 99%